2017
DOI: 10.1038/s41598-017-00722-7
|View full text |Cite
|
Sign up to set email alerts
|

The signs of Antarctic ozone hole recovery

Abstract: Absorption of solar radiation by stratospheric ozone affects atmospheric dynamics and chemistry, and sustains life on Earth by preventing harmful radiation from reaching the surface. Significant ozone losses due to increases in the abundances of ozone depleting substances (ODSs) were first observed in Antarctica in the 1980s. Losses deepened in following years but became nearly flat by around 2000, reflecting changes in global ODS emissions. Here we show robust evidence that Antarctic ozone has started to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 41 publications
2
70
2
Order By: Relevance
“…Other studies also indicated some early sign of ozone recovery in Antarctic spring and summer (Salby et al, 2011;Kuttippurath and Nair, 2017). September and October are months when the ozone hole gets largest and total ozone above…”
Section: Trends In Polar Springmentioning
confidence: 99%
“…Other studies also indicated some early sign of ozone recovery in Antarctic spring and summer (Salby et al, 2011;Kuttippurath and Nair, 2017). September and October are months when the ozone hole gets largest and total ozone above…”
Section: Trends In Polar Springmentioning
confidence: 99%
“…Multiple studies have shown signs of Antarctic ozone recovery (Kuttippurath & Nair, 2017;Solomon et al, 2016;Strahan and Douglass, 2018). This caused concern since stratospheric ozone shields the Earth's surface from DNA damaging radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also indicated some early signs of ozone recovery in Antarctic spring and summer (Salby et al, 2011;Kuttippurath and Nair, 2017). September and October are months when the ozone hole area reaches its maximum and total ozone above Antarctica exhibits minimum values (see https://ozonewatch.gsfc.nasa.gov/meteorology/SH.…”
Section: Trends In Polar Springmentioning
confidence: 99%